Pouvoir royal et sociétés dans la couronne d’Aragon. Un essai de lectura historiographique (1990-2006) - Péquignot, Stéphane (En la España Medieval, 2007)
This article’s primary objective is to define the main lines of historiographical developments taking place between 1990 and 2006 regarding royal power and its relations with the societies of the Crown of Aragon. To this end, subjects examined successively are researchers’ different interpretive models of the whole; new perspectives on monarchical institutions and the exercise of power; reflections on the articulations between royal power and other powers in the Crown of Aragon; contributions of studies focused on other groups to the understanding of royal power. The bibliography collected complements this analysis and provides a tool for scholars interested in deepening their knowledge of the Crown of Aragon